2014
DOI: 10.1103/physrevlett.113.268002
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Theory for Negative Differential Mobility in Crowded Environments

Abstract: We study the behavior of the stationary velocity of a driven particle in an environment of mobile hard-core obstacles. Based on a lattice gas model, we demonstrate analytically that the drift velocity can exhibit a nonmonotonic dependence on the applied force, and show quantitatively that such negative differential mobility (NDM), observed in various physical contexts, is controlled by both the density and diffusion time scale of obstacles. Our study unifies recent numerical and analytical results obtained in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
87
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 44 publications
(81 reference statements)
10
87
1
Order By: Relevance
“…(14) and (15), and using the definition (10), one can explicitly obtain the TP velocity in the dilute limit, for arbitrary choice of jump probabilities and time scales τ, τ * . Notice that the comparison between the expression for V (F ) obtained in the dilute limit for unconfined geometries [44], following a computation analogous to that reported here, and the analytical result of [41], revealed that the decoupling approximation is indeed exact at lowest order in ρ, for arbitrary values of the time scales τ, τ * . We claim that this statement also holds for confined geometries.…”
Section: Linearized Solution In the Dilute Regimementioning
confidence: 99%
See 4 more Smart Citations
“…(14) and (15), and using the definition (10), one can explicitly obtain the TP velocity in the dilute limit, for arbitrary choice of jump probabilities and time scales τ, τ * . Notice that the comparison between the expression for V (F ) obtained in the dilute limit for unconfined geometries [44], following a computation analogous to that reported here, and the analytical result of [41], revealed that the decoupling approximation is indeed exact at lowest order in ρ, for arbitrary values of the time scales τ, τ * . We claim that this statement also holds for confined geometries.…”
Section: Linearized Solution In the Dilute Regimementioning
confidence: 99%
“…It is expected to hold in the dilute regime, ρ ≪ 1, and for values of τ * not too large with respect to τ , namely when the dynamics of bath particles is sufficiently fast. More specifically, it has been shown that this approximation provides exact results for V (F ) in the limits of very low and very high densities in unconfined geometries [44]. Notice that the regime of validity of the approximation can be dependent on the specific choice of transition rates.…”
Section: A General Formalismmentioning
confidence: 99%
See 3 more Smart Citations